Reaction of Desulfovibrio vulgaris Two-Iron Superoxide Reductase with Superoxide: Insights from Stopped-Flow Spectrophotometry - Huang, Victor W; Emerson, Joseph P; Kurtz, Donald M (Biochemistry (Easton), 2007)
Stopped-flow mixing of the Desulfovibrio vulgaris two-iron superoxide reductase (2Fe-SOR) containing the ferrous active site with superoxide generates a dead time intermediate whose absorption spectrum is identical to that of a putative ferric−hydroperoxo intermediate previously observed by pulse radiolysis. The dead time intermediate is shown to be a product of reaction with superoxide and to be generated at a much higher proportion of active sites than by pulse radiolysis. This intermediate decays smoothly to the resting ferric active site (∼30 s-1 at 2 °C and pH 7) with no other detectable intermediates. Deuterium isotope effects demonstrate that solvent proton donation occurs in the rate-determining step of dead time intermediate decay and that neither of the conserved pocket residues, Glu47 or Lys48, functions as a rate-determining proton donor between pH 6 and pH 8. Fluoride, formate, azide, and phosphate accelerate decay of the dead time intermediate and for azide or fluoride lead directly to ferric−azido or −fluoro complexes of the active site, which inhibit Glu47 ligation. A solvent deuterium isotope effect is observed for the azide-accelerated decay, and the decay rate constants are proportional to the concentrations and pK a values of HX (X- = F-, HCO2 -, N3 -). These data indicate that the protonated forms of the anions function analogously to solvent as general acids in the rate-determining step. The results support the notion that the ferrous SOR site reacts with superoxide by an inner sphere process, leading directly to the ferric−hydroperoxo intermediate, and demonstrate that the decay of this intermediate is subject to both specific- and general-acid catalysis.